On the Safety of Construction of Buildings and Structures in Difficult Soil Conditions - Akhmedov, Ikromali; Mirkhasilova, Zulfiya; Usmanov, Shavkat (European Journal of Life Safety and Stability (2660-9630), 2022)
The article shows the impact of soil and water conditions on the safety of buildings and structures and provides recommendations for improvement.